Measurements and modeling of airborne plutonium in Subarctic Finland between 1965 and 2011 - Salminen-Paatero, Susanna; Vira, Julius; Paatero, Jussi (Atmospheric Chemistry and Physics, 2020)
The activity concentrations of 238,239,240Pu and 241Am (for determining its mother nuclide, 241Pu) as well as activity ratios of 238Pu/239+240Pu, 241Pu/239+240Pu and 239+240Pu/137Cs and the mass ratio of 240Pu∕239Pu were determined from air filter samples collected in Rovaniemi (Finnish Lapland) in 1965 to 2011. The origin of plutonium in surface air was assessed based on these data from long time series. The most important Pu sources in the surface air of Rovaniemi were atmospheric nuclear-weapon testing in the 1950s and 1960s, later nuclear tests in 1973–1980 and the SNAP-9A satellite accident in 1964, whereas the influence from the 1986 Chernobyl accident was only minor. Contrary to the alpha-emitting Pu isotopes, 241Pu from the Fukushima accident in 2011 was detected in Rovaniemi. Dispersion modeling results with the SILAM (System for Integrated modeLling of Atmospheric composition) model indicate that Pu contamination in northern Finland due to hypothetical reactor accidents would be negligible in the case of a floating reactor in the Shtokman natural gas field and relatively low in the case of an intended nuclear power plant in western Finland.